Initialization by a Novel Clustering for Wavelet Neural Network as Time Series Predictor. (22nd April 2015) - Cheng, Rong; Hu, Hongping; Tan, Xiuhui; Bai, Yanping
Abstract : The architecture and parameter initialization of wavelet neural network are discussed and a novel initialization method is proposed. The new approach can be regarded as a dynamic clustering procedure which will derive the neuron number as well as the initial value of translation and dilation parameters according to the input patterns and the activating wavelets functions. Three simulation examples are given to examine the performance of our method as well as Zhang's heuristic initialization approach. The results show that the new approach not only can decide the WNN structure automatically, but also provides superior initial parameter values that make the optimization process more stable and quickly.